The English - Indonesian Adaptation of Cultural Terminologies, Vocabularies and Phrases in Webster’s Reflection on Raden Ajeng Kartini - Rais, Azka Iftiani; Hartono, Rudi; Joko Yulianto, Henrikus (Universitas Negeri Semarang, 2021)
The aim of the research is to analyze the adaptation of terminologies, vocabularies and phrases from English to Indonesian. The research was descriptive qualitative research in order to answer the research problem definitely. The data of the study were taken from a biography written by Tracy Wright Webster entitled Reflection on Raden Ajeng Kartini, while the translation is done by the author itself. The total number of data found was 75 Javanese cultural concepts. Then, the data were grouped into several culture categories before presented in the analysis. The result shows that there are three basic aspects that determine the translator in carrying the adaptation strategy with the Javanese culture. Those aspects are cultural factor, linguistic factor and the translator's preference. The aspects influencing the translation strategy that the translator carries is language and Indonesian modern history. In conclusion, the translation strategy of adaptation that is carried by the translator is actually dynamic. It is because in translating the Javanese cultural concepts are alternated or even hybridized, depending upon the translator's intention whether she wants to introduce the cultural concepts to the TL reader or not. However, apart from the limitation of the biography of Reflection on Raden Ajeng Kartini translation, the English version is still important for foreigners to know more about Indonesian history, culture and society.